Определение частот и форм собственных колебаний жидкости в составных резервуарах - Троценко, Ю.В. (Нелінійні коливання, 2015)
Розвинуто варiацiйний метод розв’язання спектральної задачi про вiльнi коливання рiдини в осесиметричному резервуарi складної геометрiї, що поставлена з позицiй методу спряження. Отримано узагальнений функцiонал, для якого умови спряження на сумiжнiй частинi введених пiдобластей є природними граничними умовами. За допомогою методу Трефтца розв’язання вихiдної задачi зведено до розв’язання алгебраїчної задачi невеликої розмiрностi. Наведено результати розрахункiв, якi демонструють ефективнiсть запропонованого пiдходу. We develop a variation method for solving a spectral problem for free oscillations of fluid in a complex geometry reservoir having an axis symmetry. The problem is formulated as to use the bridging method. We obtain a generalized functional such that the conjugacy conditions on the bordering parts of the introduced domains make natural boundary-value conditions. We use the Trefts method to reduce the initial problem to a problem of solving an algebraic problem the dimension of which is not too large. The calculations performed show effectiveness of the proposed method.